Helping Aged Victims of Crime (the HAVoC Study): Common Crime, Older People and Mental Illness. Issue 2 (20th January 2015) - Serfaty, Marc; Ridgewell, Anna; Drennan, Vari; Kessel, Anthony; Brewin, Chris R.; Wright, Anwen; Laycock, Gloria; Blanchard, Martin
Abstract : Backgound: Limited data suggest that crime may have a devastating impact on older people. Although identification and treatment may be beneficial, no well-designed studies have investigated the prevalence of mental disorder and the potential benefits of individual manualized CBT in older victims of crime.Aims: To identify mental health problems in older victims of common crime, provide preliminary data on its prevalence, and conduct a feasibility randomized controlled trial (RCT) using mixed methods.Method: Older victims, identified through police teams, were screened for symptoms of anxiety, depression or post-traumatic stress disorder (PTSD) one ( n = 581) and 3 months ( n = 486) after experiencing a crime. Screen positive participants were offered diagnostic interviews. Of these, 26 participants with DSM-IV diagnoses agreed to be randomized to Treatment As Usual (TAU) or TAU plus our manualized CBT informed Victim Improvement Package (VIP). The latter provided feedback on the VIP.Results: Recruitment, assessment and intervention are feasible and acceptable. At 3 months 120/486 screened as cases, 33 had DSM-IV criteria for a psychiatric disorder; 26 agreed to be randomized to a pilot trial. There were trends in favour of the VIP in all measures except PTSD at 6 months post crime.Conclusions: This feasibility RCT is the first step towards improving the lives of older victims of common crime. Without intervention, distress at 3 and 6 months after a crime remains high. However, the well-received VIP appeared promising for depressive and anxiety symptoms, but possibly not posttraumatic stress disorder.